2002
DOI: 10.7164/antibiotics.55.814
|View full text |Cite
|
Sign up to set email alerts
|

Hexacylinol, a New Antiproliferative Metabolite of Panus rudis HKI 0254.

Abstract: During our continuing screening for new bioactive metabolites from fungi we discovered recently hexacyclinol(1) as a novel, unusual, oligocyclic metabolite in cultures of the fungal strain Panus rudis HKI 0254. The strain was isolated from basidiospores of this fungus found on dead betula woods collected near Irkutsk (Sibiria, specimen herb. H, DORFELT, Sibiria 299). Panus rudis is of widespread occurrence throughout the world in many different ecotypes and has been reported to produce bioactive secondary meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
65
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 3 publications
12
65
1
1
Order By: Relevance
“…Finally, treatment of 139 with K10 clay generated the target compound 138 following a S N 2'/ cyclization path. The NMR data of the synthetic sample, whose structure was confirmed by X-ray analysis, was identical to those reported by Gräfe and co-workers 63 for hexacyclinol. 68 After this work, there were two synthesis of remarkably different structures (134 and 138), for which both were claimed having identical NMR data compared to natural hexacyclinol.…”
Section: Hexacyclinolsupporting
confidence: 68%
See 1 more Smart Citation
“…Finally, treatment of 139 with K10 clay generated the target compound 138 following a S N 2'/ cyclization path. The NMR data of the synthetic sample, whose structure was confirmed by X-ray analysis, was identical to those reported by Gräfe and co-workers 63 for hexacyclinol. 68 After this work, there were two synthesis of remarkably different structures (134 and 138), for which both were claimed having identical NMR data compared to natural hexacyclinol.…”
Section: Hexacyclinolsupporting
confidence: 68%
“…In 2002, Udo Gräfe and co-workers 63 isolated a novel compound from the fungal strain Panus rudis HKI 0254 and termed it hexacyclinol. The structural elucidation, which relied on different techniques such as high resolution mass spectrometry (HRMS), infrared (IR) and NMR, including 1 H, 13 C, distortionless enhancement by polarization transfer (DEPT), COSY, HMQC, HMBC and NOESY experiments, led to the proposal depicted in Figure 27.…”
Section: Hexacyclinolmentioning
confidence: 99%
“…315 The structure of hexacyclinol was subsequently revised, and an alternative structure 541 was confirmed via total synthesis. In addition, an X-ray crystal structure was obtained, providing unequivocal structural confirmation.…”
Section: Othersmentioning
confidence: 99%
“…[1] The proposed structure contains both reactive epoxyketone and highly strained endoperoxide moieties. A synthesis of the structure proposed by Gräfe and co-workers, as well as preliminary evaluation of non-peroxide-containing precursors as antimalarial agents, was recently reported by La Clair.…”
mentioning
confidence: 99%
“…Under these conditions, "pre-hexacyclinol" (4) was cleanly obtained in 87 % yield as a single diastereomer. [5,10] To assess the transformation [7] of panepoxydon (6) to monomeric precursor 5, we treated commercially available [16] 6 with K10 clay in CD 3 OD (40 8C, 10 h) which afforded epoxyquinol diene monomer 5 (60 % conversion according to 1 H NMR spectroscopy). [11] After considerable experimentation, we found that the final S N 2' substitution/cyclization of 4 to hexacyclinol (2) was efficiently mediated by K10 clay [17] (EtOAc, room temperature, 3 min, 99 %).…”
mentioning
confidence: 99%